Effect of Parent–Child Attachment on College Students' Social Anxiety: A Moderated Mediation Model. Issue 6 (December 2020) - Yu, Yi; Liu, Shen; Song, Minghua; Fan, Hang; Zhang, Lin
This study investigated the relationship between parent–child attachment and social anxiety in college students, as well as the mediating role of psychological resilience and the moderating role of online social support. In total, 614 college students were recruited by the cluster sampling method. The results showed that (1) parent–child attachment was negatively correlated with college students' social anxiety and positively correlated with their psychological resilience, (2) psychological resilience played a mediating role between parent–child attachment and college students' social anxiety, and (3) online social support regulated the first half and second half of the mediation process in which parent–child attachment affected college students' social anxiety through psychological resilience. These findings revealed the mechanism of parent–child attachment affecting social anxiety, which had important theoretical and empirical value for enhancing the strength of college students' psychological resilience and alleviating social anxiety.